Kesulitan Belajar: Gangguan Psikologi pada Siswa dalam Menerima Pelajaran - Ayu Putri Utami (ScienceEdu: Jurnal Pendidikan IPA, 2020)
This research study aims to find out the inter-student relationships available in psychological disorders in education. The method used in this study is literature study. Where the technique used is the literature content analysis technique. And to maintain the accuracy of a data, the reading of the library is done and checking the existing library data. Where things will be involved are learning difficulties. Learning difficulties that are often carried out by children or students in the teaching and learning process. Teachers who have given the same lessons and the same method to students in one class but still have students who cannot absorb the lessons well even though they have the same perfect ones if they are seen with ordinary eyes. This is what found learning difficulties to exist. Where learning difficulties and student development will produce obstacles in information. Learning difficulties are internal and external factors. In this case, learning difficulties can be done because students relate to the psyche of students or with different learning with learning difficulties due to physical factors or physical disabilities. And the teacher must have the ability to discuss students who discuss learning difficulties. Where before solving the problem, the teacher must find out the causes of learning difficulties occur in a student. And if you already know the learning factors from which the teacher can provide different methods in each material that will be taught.